Incidentally Detected Rare Retroperitoneal Tumor: Ganglioneuroma - Khalequezzarnan, Syed; Ahsan, Sania; Khandker, Dilruba; Khan, Biva Shrestha; Huda, Atia (Pulse, 2022)
A primary extra-adrenal retroperitoneal ganglioneuroma was found incidentally in a 22-year-old woman during screening for suspected pregnancy by transvaginal ultrasonography (TVS) and subsequently by magnetic resonance imaging (MRI). TVS and MRI revealed well defined solid mass in retroperitoneal at the level of L5 to S2 vertebrae and displace right common iliac and external iliac vessels. Limited cuts of the region of Computed tomography (CT) were taken and no calcification was identified. Histological examination showed that the lesion was an extra-adrenal retroperitoneal ganglioneuroma composed of mature ganglion cells and subsequently confirmed by immunohistochemistry. Pulse volumel.11 January-December 2018-2019 p.13-18